DEVELOPING ENGLISH LEARNING MATERIALS FOR FRONT OFFICE STUDENTS IN TOURISM FACULTY OF TRIATMA MULYA UNIVERSITY - Ni Putu Artila Dewi; Ni Made Dita Sinta Dewi; Komang Meliawati (Universitas Triatma Mulya, 2021)
Teaching English especially in front office department was less textbook and dominated by memorization of vocabularies. This research aims to develop English learning materials in the form of textbook for front office students in Tourism Faculty, Triatma Mulya University. The method of the current study is Design and Development. In developing the learning material, this research uses the DnD model by Richey and Klein. Some processes were carried out, namely identifying learning materials needed, developing learning materials in the form of books and evaluating the results of material development. The results of the study found that there are six types of material that need by front office students namely (1) front office department coordination to other departments, (2) telephone operator, (3) reservations, (4) reception, (5) porter/uniformed service, and (6) procedure handling complaint. The results of expert tests showed the score of the learning material developed belongs to good category.